La influencia de la calidad de servicio logístico en la lealtad: Un análisis del papel moderador de las TIC - D. Servera Francés; Irene Gil Saura; M. Fuentes Blasco (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2009)
This paper focuses on the study of the ICT applied to the role of logistics in companies relationships, therefore a deeper analysis will be carried out on how the ICT affect the traditional chain of consequences: Service Quality - Value - Satisfaction - Loyalty. The SEM analysis is used in order to contrast the hypotheses of the links proposed bearing in mind the high/low presence of the ICT. The results on the reliability and validation analysis of the scales used are satisfactory and our conclusions confirm the above mentioned chain of consequences and remark the ICT influence when describing these relations.
Keywords: 330; ICT; logistics; supply Relationships; logistics service quality; logistics value